Are workplace factors associated with employee alcohol use? The WIRUS cross-sectional study - Lisebet Skeie Skarpaas; Randi Wågø Aas; Mikkel Magnus Thørrisen; Tore Bonsaksen; Jens Christoffer Skogen (BMJ Open, 2022)
Objectives Sociodemographic predictors of employee alcohol use are well established in the literature, but knowledge about associations between workplace factors and alcohol use is less explored. The aim of this study was to explore whether workplace factors were associated with employee alcohol use (consumption and alcohol-related problems).Design Cross-sectional study. Linear and binary logistic regression analyses.Setting Heterogeneous sample of employees (workers and supervisors) from 22 companies across geographical locations and work divisions in Norway.Participants Employees (N=5388) responded on survey items measuring workplace factors and alcohol use.Outcomes Data on alcohol use were collected with the Alcohol Use Disorders Identification Test (AUDIT). Consumption was measured with the AUDIT-C (the first three items), and alcohol-related problems were operationalised as a sum score of 8 or higher on the full 10-item AUDIT.Results Higher levels of alcohol consumption were associated with more liberal workplace drinking social norms (b=1.37, p<0.001), working full-time (b=0.18, p<0.001), working from holiday home (b=0.40, p<0.01), being a supervisor (b=0.25, p<0.001), having supervisors with less desired leadership qualities (b=−0.10, p<0.01), shorter working hours (b=−0.03, p<0.05), higher workplace social support (b=0.13, p<0.05) and higher income (b=0.02, p<0.001). Alcohol-related problems were associated with more liberal workplace drinking social norms (OR=3.52, p<0.001) and shorter working hours (OR=0.94, p<0.05).Conclusions Workplace drinking social norms were the supremely most dominant predictor of both consumption and alcohol-related problems. Results suggest that some workplace factors may play a role in explaining employee alcohol consumption, although the predictive ability of these factors was limited. This study points to the importance of drinking social norms, workplace drinking culture and leadership for understanding employee alcohol use.